Evangelistic praying - MacArthur, John, 1939- (USA : Word of grace communications, 1988)
Bible studies taken from messages delivered at Grace Community Church in Panorama City, California.
Includes indexes.
Keywords: Bible. N.T. Timothy, 1st, II, 1-8 -- Criticism, interpretation, etc; Bible. N.T. Matthew IX, 35-X, 1 -- Criticism, interpretation, etc; Evangelistic work -- Biblical teaching; Prayer -- Biblical teaching